Lixiviación de concentrados Pb/Ag con alto contenido de As/Sb - Azañero Ortiz, Ángel (2004)
In the northern and central zones of Peru there exist minerals of Pb-Ag that contain high amounts of As-Sb; by flotation one can not eliminate these elements and they yield in the concentrate of flotation; from 0.5% to 2.0% they receive economic losses for each additional 0.10%; up to 3% the losses are more severe and at times difficult to place it in the market; major percentages of arsenic and antimony simply are rejected for smelting; in this research work we float a mineral of lead-silver, producing a concentrate with high amounts of impurities, said product, called unclean concentrate was leached out with sodium hydroxide and sodium sulfide at different concentrations of the reactants, dilution of pulp and time of retention, determining the optimal conditions of leaching, obtaining a clear concentrate with higher grades of Pb-Ag (Table N.° 6) for easy commercialization. The flow diagram proposed to process similar minerals to the study is on Figure N.° 4.